PENINGKATAN PENGENALAN SAINS SEDERHANA MELALUI METODE DEMONSTRASI ANAK USIA 5-6 TAHUN - (F54210014), Faradila; Thamrin, M.; ., Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Based on the research that has been done and through the results obtained after an analysis of data that: 1) Planning to improve the recognition capability of learning simple science demonstration method in children can be categorized as